Micro Tribological Investigations on Dry Sliding Friction of 100Cr6 Axial Bearing Surfaces - Florian Pape (Japanese Society of Tribologists, 2016)
A detailed knowledge of the interface between a sliding ball and an axial bearing surface allows to shed light on how to reduce friction and wear in bearings under slippage conditions. To study the interface, the contact was investigated applying micro-pin-on-disk tests without grease or oil lubrication. As pins sapphire half-balls and 100Cr6 steel bearing balls were used. As counterpart unused 100Cr6 steel (German standard corresponding to AISI52100) axial bearing surfaces were applied. It could be shown, that with the formation of surface layers, the frictional force was reduced. This effect is lower in case of a chemical inert sphere as contact partner. The transition from friction to stiction for varied Hertzian stress was observed. The spheres on the micro-pin-on-disk tester measured the frictional properties of the surface without ploughing effects. The micro-pin-on-disk tests allow to have a closer look on the start behavior of a metallic and sapphire test specimen on an axial bearing washer under ambient conditions.